2015
DOI: 10.5797/jnet.cr.2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Use of a superficial temporal vein approach for transvenous embolization of a cavernous sinus dural arteriovenous fistula: a case report

Abstract: Objective: The inferior petrosal sinus (IPS) provides the best access route to the cavernous sinus in transvenous embolization (TVE) of cavernous sinus dural arteriovenous fistula (CS-dAVF). However, some cases require other access routes. We describe a case of CS-dAVF successfully treated with TVE via the superficial temporal vein (STV) from the common femoral vein. Case presentation: The patient was an 82-year-old woman with conjunctival hyperemia and exophthalmos of the left eye due to a left CS-dAVF. A cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…[ 12 , 20 ] It has been reported that IPS was the most selected access route to the CS and could approach the CS in 90% of patients. [ 20 ] However, when the IPS is inaccessible or it is difficult to treat the CSDAVF with TVE through the IPS route, various alternative access routes, such as the superior petrosal sinus,[ 16 ] the pterygoid plexus,[ 9 ] the facial vein (FV),[ 3 , 13 ] and the STV,[ 8 ] have been reported. The usefulness of direct puncture of the SOV,[ 2 ] FV,[ 1 , 15 ] STV,[ 11 ] and frontal vein,[ 19 ] and direct puncture of the Sylvian vein by craniotomy[ 14 ] has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 20 ] It has been reported that IPS was the most selected access route to the CS and could approach the CS in 90% of patients. [ 20 ] However, when the IPS is inaccessible or it is difficult to treat the CSDAVF with TVE through the IPS route, various alternative access routes, such as the superior petrosal sinus,[ 16 ] the pterygoid plexus,[ 9 ] the facial vein (FV),[ 3 , 13 ] and the STV,[ 8 ] have been reported. The usefulness of direct puncture of the SOV,[ 2 ] FV,[ 1 , 15 ] STV,[ 11 ] and frontal vein,[ 19 ] and direct puncture of the Sylvian vein by craniotomy[ 14 ] has also been reported.…”
Section: Discussionmentioning
confidence: 99%